Incidental Finding and Endovascular Repair of a Left Internal Mammary Artery Aneurysm following a Multivessel Coronary Artery Bypass Graft - Osayi Lawani; Jiries Ganim; Rick Ganim (Case Reports in Cardiology)
True aneurysms discovered within the internal mammary artery are extremely rare and typically have an asymptomatic occurrence. Their presentation and management have also been variable due to their low incidence, decreased detection, or lack of documentation. They have a high risk for morbidity or mortality as they can possibly rupture with increasing size and thus become life-threatening. Coronary CT angiography is the most definitive test for confirming and finding complications related to the aneurysm. With an increase in the aging population and advancement in the techniques used in coronary artery bypass grafting, it is likely that the rate of recorded occurrence of aneurysms and pseudoaneurysms will increase. Endovascular repair is currently the most favored treatment modality. In this report, we describe a case of a 74-year-old male who was incidentally found to have a left internal mammary artery aneurysm following complaints of chest pain related to another nearly occluded grafted vessel. To the best of our knowledge, and following an extensive literature review, this is likely the first documented case of a true aneurysm found within a left internal mammary artery bypass graft. The patient recovered well following placement of a covered stent; however, upon follow-up one year later, he was found to have stenosis of the same vessel, which was subsequently treated without further complication.